Identification Of Keywords That Impact Of Increasing The Click Through Rate Of Online Advertising On Search Engines - Aris Wahyu Murdiyanto; Arif Himawan; Aris Wahyu Murdiyanto (Jurusan Teknik Informatika, 2022)
Purpose: To identify keywords that can be chosen to increase CTR on the website so that the potential revenue of targeted prospects through search engines is higher.Design/methodology/approach: This study applies the weighted product method based on the criteria that will be determined to find the best keyword list.Findings/result: The results of identification by ranking using the weighted product method based on the criteria C1, C2, and C3 resulted in an average increase in CTR of 16.18% to 22.92%. With this increase, business owners can be more efficient in the online advertising process.Originality/value/state of the art: The identification of keywords that can be chosen to increase CTR on a website by ranking using the weighted product method has never been done by previous researchers.